Chibụike Ụzọma - to kick a stone - Sapera, Kat (Anomie Publishing, 2023)
Comprising colourful, abstruse portraitures against stark black and white backgrounds, the paintings in To Kick a Stone are deeply suggestive, but ultimately formalist explorations of shape and composition. Functioning as prompts, the paintings play on our proclivity to anthropomorphise and personify images. Probing the relationship between pictorial illusion, individual shapes and complete images, Uzoma's new works are often bordered with lettering that doubles as a compositional element and an evocative detail for viewers to delve into. Central to this body of work are the philosophical implications of Roland Barthes' 1967 essay The Death of The Author, which rejected the idea that a work of art should be analysed in relation to the artist's intent and personal history; instead proposing that meaning is activated by the viewer. As such, these works are deeply collaborative. Whilst Uzoma is primarily focused on the peculiarities of painting, it is his understanding that audiences will bring varied cultural references and perspectives to the works, synergistically developing narratives that evolve from moment to moment, with viewer to viewer. -- https://www.simonleegallery.com/exhibitions/248/press_release
Keywords: Uzoma, Chibuike -- 1992-; Ụzọma, Chibụike / Exhibitions; Ausstellungskatalog -- Simon Lee Gallery, London -- 19.01.2023-25.02.2023 -- London; Gespräch